Monozygotic Twins Concordant for Common Variable Immunodeficiency: Strikingly Similar Clinical and Immune Profile Associated With a Polygenic Burden - Silva, Susana L.; Fonseca, Mariana; Pereira, Marcelo L. M.; Silva, Sara P.; Barbosa, Rita R.; Serra-Caetano, Ana; Blanco, Elena; Rosmaninho, Pedro; Pérez-Andrés, Martin; Sousa, Ana Berta; Raposo, Alexandre A. S. F.; Gama-Carvalho, Margarida; et al. (Frontiers in Immunology, 2019)
Monozygotic twins provide a unique opportunity to better understand complex genetic diseases and the relative contribution of heritable factors in shaping the immune system throughout life. Common Variable Immunodeficiency Disorders (CVID) are primary antibody defects displaying wide phenotypic and genetic heterogeneity, with monogenic transmission accounting for only a minority of the cases. Here, we report a pair of monozygotic twins concordant for CVID without a family history of primary immunodeficiency. They featured a remarkably similar profile of clinical manifestations and immunological alterations at diagnosis (established at age 37) and along the subsequent 15 years of follow-up. Interestingly, whole-exome sequencing failed to identify a monogenic cause for CVID, but unraveled a combination of heterozygous variants, with a predicted deleterious impact. These variants were found in genes involved in relevant immunological pathways, such as JUN, PTPRC, TLR1, ICAM1 and JAK3. The potential for combinatorial effects translating into the observed disease phenotype is inferred from their roles in immune pathways, namely in T and B cell activation. The combination of these genetic variants is also likely to impose a significant constraint on environmental influences, resulting in a similar immunological phenotype in both twins, despite exposure to different living conditions. Overall, these cases stress the importance of integrating NGS data with clinical and immunological phenotypes at the single-cell level, as provided by multi-dimensional flow-cytometry, in order to understand the complex genetic landscape underlying the vast majority of patients with CVID, as well as those with other immunodeficiencies.